STRATEGI GURU PAI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENGEMBANGKAN KARAKTER KEDISIPLINAN PESERTA DIDIK PADA MASA COVID-19 - Ilmi Rodhiyatul Aulia; Abd Jalil; Fita Mustafida (VICRATINA, 2021)
The strategy of PAI teachers in building action discipline character education is one of the important factors that must be applied during the covid-19 period with the aim of stimulating, motivating, encouraging students to carry out distance learning. Meanwhile, the purpose of this study is to find out the strategy of PAI teachers in building discipline character education for students during the covid-19 period, and the implementation of action discipline character education in some material in clas VIII that was applied by PAI teachers at SMP Negeri 1 Kepanjen. This study uses descriptive methods, data collection techniques in the form of observation, interviews, and documentation. The subject of the research were the VIII grade PAI teachers, and VIII grade students at SMP Negeri 1 Kepanjen. Data analysis was carried out qualitatively, the results of this study indicate that: (1) The strategies used include providing enthusiasm and motivation, assigning tasks, responsibilities and disciplined actions. (2) Meanwhile, in the implementation of the action discipline character education strategy related to the even semester VIII material, the focus is more on the learning strategy, and the results of the effort to build a character education strategy for the discipline of action, namely: the discipline of choosing healthy and halal food and drinks, on time in worship, discipline in doing tasks, discipline in doing good deeds and husnudzon.   Kata Kunci: The strategy of PAI teachers, Action discipline character education, The covid-19 period